„.I have the right to feel differently.“ Mindplay in the preschool - Elídóttir, Jórunn; Zophoníasdóttir, Sólveig (Menntavísindasvið Háskóla Íslands, 2020)
This article is based on the research- and development project; Mindplay- conversation for learning. The project was a collaboration between the preschool Lundarsel in Akureyri, the Centre for School Development and the Faculty of Education at the University of Akureyri.The main objective of the project was that preschool staff learned about different means to use conversation with children to enhance their ability and skills in using conversational practice with children in daily life in school. Secondly, to study the effect of these methods for the daily practice and the children’s use of language in discussions. The focus is on how to use language as a tool for thinking collectively and to help the children to use language effectively in every day learning processes.The project fits well with education policy as it appears in the general section of the National Curriculum Guide, emphasizing that schools promote children’s and young people’s ability to draw conclusions, take positions on data and information, and apply critical thinking in the formulation and dissemination of ideas in a creative way. The national curriculum for preschools emphasizes that there should be a forum in the preschool where everyone actively engages in public discussion, people listen to one another and exchange views.The Lundarsel project covered a two-year period including eight dialogue lessons with the teachers. The lessons involved an introduction to different conversation methods, preparation for conversation practice with the children, and drawing out a lesson plan for their work, as well as the teachers reflecting on how things were going and the learning process among themselves and the children. The preschool teachers handed in several curriculums for the Circle Times during the two years’ practice. In the final sessions, the participants participated in a focus group interview to evaluate the project as a whole. Lundarsel is a four classroom preschool with about 89 children and 25 employees. The proportion of preschool ...